Exploring Language Proficiency Enhancement Trainings of Call Center Agents: Unveiling BPO Trainer Strategies from Agents’ Standpoints - Calderon, Angel Love R.; Mandabob, Hannah Kristel; Maroto, Joanna Mae G.; Syting, Christian Jay O. (International Journal Corner of Educational Research, 2025)
This study investigated the strategies trainers use in language proficiency enhancement training, as perceived by student call center agents. It specifically examined strategies for developing the four macro skills (listening, speaking, reading, and writing) and grammar skills. Using thematic analysis, it was found that various strategies were employed. Firstly, reading strategies involve active reading and practice reading. Secondly, in terms of writing, their strategies were the process-based approach and the rule-based strategy. Thirdly, the strategy used in listening was active listening. Fourthly, the speaking strategies involved simulation and speaking tests. Lastly, for grammar skills, the strategy used was direct instruction. Participants also shared insights on the training they received from BPO companies, which included challenges in understanding diverse communication styles, struggles with fluent and natural communication, and language acquisition and development strategies. The results imply that understanding call center agents’ perspectives on language training can enrich the curriculum by offering effective strategies, such as hands-on simulated activities, active learning, and student-centered pedagogies, optimizing learning experiences and fostering more effective communication skills. Furthermore, the results underscore the importance of using learner input to continually evolve and optimize curriculum design, emphasizing the transformative impact of learning and learner-centered approaches on educational practices.